PENGARUH TINGKAT PENDIDIKAN DAN PENDAPATAN ORANG TUA TERHADAP MOTIVASI BELAJAR SISWA KELAS X SMA NEGERI 15 PEKANBARU - Nurhabibah Nurhabibah; Sakdanur Nas; Fenny Trisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of this study was a difference between expectations and reality occurred at class X SMA Negeri 15 Pekanbaru, wherein the low motivation of student learning in the classroom. The purpose of this study was to determine and analyze how the effect of education and income levels of parents of student motivation at class X in SMA Negeri 15 Pekanbaru. The population of this study all student in grade X as many as 182 students.The study sample as many as 64 students were calculated using the formula Slovin. Data collection methods used were questionnaires. Method of data analysis are multiple regressions analysis. Based on the result of analysis data is concluded has effect and significant among parental education (X1) and income of parents (X2) on student motivation (Y). Based on R square table showed 0,178 it means independent variable used in this study has effect on dependent variable as many as 17,8 %. Therefore, ability independent variable for influence dependent variable is weak. This is due to many another variables which influence dependent variable. Partially, the education level of parents do not have a significant influence on student motivation with significance values of 0,587 greater than 0,05. While the parents income has a significant influence on student motivation with significance values of 0,002 less than 0,05.Key Words: Parental Education, Income of Parents, Student Motivation